On-campus and distance students inthe compulsory teacher education program at the University of Iceland School of Education: Background, attitudes and commitment to the teaching profession - Jóhannsdóttir, Þuríður Jóna; Björnsdóttir, Amalía (Menntavísindasvið Háskóla Íslands, 2019)
In Iceland, 5 years of university education are required to qualify as a compulsory school teacher. Teacher education is offered at the University of Iceland (UI) in Reykjavík, and at the University of Akureyri in North Iceland. The focus of this article is compulsory teacher education at the University of Iceland. Student teachers can choose between campus-based attendance and online learning with required periodical face-to-face sessions, and can even choose which form they prefer in each individual course. Around half of the students at UI are online students. In Iceland, like in many other countries, declining enrollment in teacher education programs has caused concern about the shortage of qualified teachers at the compulsory school level. In the 1990s, a similar situation was met by a special effort to enable universities to enroll more student teachers and to offer distance education for teachers without formal qualifications who were teaching in rural schools. As a result, the percentage of uncertified teachers decreased (especially in rural areas) and, when an economic crisis hit Iceland in 2008, teachers returned to work in compulsory schools, increasing the number of qualified teachers. However, in 2015 the number of teachers without certification started to increase once again, from 4% on average from 2011 to 2014 to 9% in 2017. The ratio of individuals dropping out from compulsory teacher education, as well as from the profession, also causes concern. Therefore, it is important to investigate which factors might be related to student teachers’ commitment to the teaching profession. Because teacher education at the University of Iceland has been offered both on-campus and as a blend of online and face-to-face, we think it is of particular interest to understand whether there is a difference between students in online and on-campus programs. This study presents a picture of the background of students in the teacher education program at the University of Iceland School of Education, and explores ...